Nuclear weapons and intergenerational exploitation - Rendall, Matthew (Taylor & Francis, 2007)
Nuclear weapons’ defenders claim that they lower the risk of war, at the price of devastation if war breaks out. But sooner or later, on a realist analysis, catastrophic nuclear war is almost sure to come. Nuclear deterrence thus buys us a better chance of dying in bed, while each post-holocaust generation will have to pick up the pieces. If the nuclear optimists are wrong, hoping to spread or perpetuate nuclear deterrence is foolish. But if they are right, it is exploitative. Like big cars and cheap flights, nuclear deterrence benefits us at the expense of future generations. States that do not already have the bomb should not get it. Britain and France should consider disarmament, while Russia and the United States should slash their arsenals. Minimum deterrence should be equally stable, but most nuclear optimists, being neorealists who hold that war will continue, should want deep cuts even if it is not.